(untitled) (Diametros, 2014)
In this paper, I develop a solution to the puzzle of mirror perception: why do mirrors appear to reverse the image of an object along a left/right axis and not around other axes, such as the top/bottom axis? I set out the different forms the puzzle takes and argue that one form of it – arguably the key form – has not been satisfactorily solved. I offer a solution in three parts: setting out the conditions in which an apparent left/right reversal of mirror images is generated; explaining why these conditions are so often met; explaining why we are cognitively biased towards the perception of left/right reversal when these conditions are met.